INFLUENCE OF LIFESTYLE AND GROUPS REFERENCE TO SIN COFFEE PALU'S LOYALTY WITH BRAND SATISFACTION AS INTERVENING VARIABLES - Aulia Salsabila; Muzakir; Umar Syarifuddin; Faruq Lamusa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study This aim For analyze Influence of Lifestyle and Groups Reference to Loyalty Customer with Brand Satisfaction as Intervening variables in Sin Coffee Palu. Research use approach quantitative with Partial Least Squares–Structural Equation Modeling (PLS-SEM) method . Data obtained through distribution questionnaire to customers and processed use SmartPLS . Research results show that Lifestyle and Group Reference influential positive and significant to Brand Satisfaction as well as Loyalty Customers . In addition , Brand Satisfaction is proven influential significant to Loyalty Customers . Other findings show that Brand Satisfaction plays a role as a significant mediator in connection between Lifestyle and Group Reference to Loyalty Customers . This result confirm that suitability style life , influence social , and level satisfaction to brand own role important in form loyalty customers at Sin Coffee. Research This expected can become references for manager in develop more marketing strategies​ effective and relevant with characteristics its consumers .